EARLY STUDY OF DIGITAL CONTROL SYSTEMS AND INFORMATION AT THE HOUSE FOR AUDIO - Deni Priatman; Aqwam Rosadi K, Skom., MM Aqwam Rosadi K, Skom., MM (Jurnal Sistem Komputer, 2001)
The digital control system will make memorable house was inhabited, althoughabandoned for a few days. This control system worked as long as 24 hours a day bymaking use of changes in light intensity.The digital control tool can be ignited or extinguished in accordance with the desireof user. These tools provide the means to control multiple electrical devices thatignited and extinguished on a certain day such as lighting, television, tape recorder orthe radio. For tape recorders to be used can be filled with an assortment of soundeffects sound like little children crying, the sound the rooster crows, the sound ofsomeone taking a bath and others.